2017
DOI: 10.1038/s41598-017-01645-z
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted catalytic hydrogenation of amides via diverse activation of a sterically confined bipyridine–ruthenium framework

Abstract: Amides are ubiquitous and abundant in nature and our society, but are very stable and reluctant to salt-free, catalytic chemical transformations. Through the activation of a “sterically confined bipyridine–ruthenium (Ru) framework (molecularly well-designed site to confine adsorbed H2 in)” of a precatalyst, catalytic hydrogenation of formamides through polyamide is achieved under a wide range of reaction conditions. Both C=O bond and C–N bond cleavage of a lactam became also possible using a single precatalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 54 publications
3
47
0
Order By: Relevance
“…Our initial studies were centred around 1,6-hexanedioate esters for two reasons. Firstly, 1,6-hexanedioate esters can be easily and sustainably obtained, either from biomass, such as glucose by catalytic or enzymatic methods, 14 , 15 or from 1,3-butadiene by palladium catalysed alkoxycarbonylation reactions. 27 – 29 The second reason for us to use 1,6-hexanedioate esters is because our initial reactions focussed on ε-caprolactam, which can be used as a precursor for the synthesis of Nylon-6.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our initial studies were centred around 1,6-hexanedioate esters for two reasons. Firstly, 1,6-hexanedioate esters can be easily and sustainably obtained, either from biomass, such as glucose by catalytic or enzymatic methods, 14 , 15 or from 1,3-butadiene by palladium catalysed alkoxycarbonylation reactions. 27 – 29 The second reason for us to use 1,6-hexanedioate esters is because our initial reactions focussed on ε-caprolactam, which can be used as a precursor for the synthesis of Nylon-6.…”
Section: Resultsmentioning
confidence: 99%
“…The groups of Crabtree, 1 Cole-Hamilton, 2 – 5 Leitner 6 and Beller 7 have reported that amides can be successfully hydrogenated to amines using Ru/triphos catalysts and that, in contrast to reactions using heterogeneous catalysts, 8 aromatic rings in the substrates remain untouched. Other catalysts for amide hydrogenation generally lead to C–N rather than C–O cleavage products giving alcohols from the carboxylate reside 9 14 or to partial reduction. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactivity of the various carbonyl compounds (amide<carboxylic acid<ester<anhydride<ketone≈aldehyde<acid chloride) was originally determined by McAlees and McCrindle, and this trend also manifests in the increasing susceptibility toward nucleophilic attacks at the carbonyl group. In order to replace conventional methods for the synthesis of amines from the corresponding amides by using unsustainable methods employing an excess of dangerous reductants such as LiAlH 4 , various homogeneous catalysts have been developed that use molecular H 2 as an ideal reductant . However, in addition to the common drawbacks of homogeneous catalysts such as problems associated with catalyst/product separation and catalyst recycling, most of those homogeneous catalysts require acidic or basic additives .…”
Section: Hydrogenation Of Amidesmentioning
confidence: 99%
“…2A). The catalytic framework generated upon addition of n H 2 (n = 1 to 6) to Ir-a maintains its structural robustness, with no detachment of the ligand from the Ir center or C─P bond cleavage (21). Thus, the complex retains good catalytic activity even under strenuous conditions [hydrogen pressure (P H2 ) = 4 to 8 MPa; reaction temperature (T) = 140° to 200°C; reaction time (t): 18 to 120 hours].…”
Section: Introductionmentioning
confidence: 99%